A case report of isolated zygomatic arch fracture by modified towel clip method. Issue 2 (26th October 2020) - Hayashi, Kamichika; Migita, Masashi; Iwasaki, Takahiro; Onda, Takeshi; Takano, Masayuki; Takaki, Takashi
Abstract: Fractures of the zygomatic arch may be treated with a variety of techniques. The disadvantages of these methods include the difficulty of reaching the fracture site via the intraoral approach and the high level of surgical invasiveness associated with the extraoral approach. This is a case report. A 20‐year‐old man was banged on the face. He presented at our department complaining of a change in facial shape and difficulty in mouth opening. Modified towel clip method was used to treat the zygomatic fracture which was classified into Yamamoto Class II type, and successful reduction was achieved. We believe that this method is very effective from the standpoint of minimum invasiveness and simplicity.